An Analysis of Ibn-Khaldun’s Theory in light of Covid-19 Pandemic - Alameri, Mohammed Musallem Binham; AL-Tkhayneh, Khawlah M. (International Journal of Criminology and Sociology, 2021)
This argumentative paper presents a new perspective on Ibn-khaldun’s theory of social change in light of Covid-19. It argues that when examining the theory, it can be found that it makes an association between social change and natural factors, such as epidemics and human factors, such as government changes. The target theory which is explored in this study is the cyclical theory of Ibn-khaldun. This study adopts the former theory in order to analyze the effects of Covid-19 on the Arab-Islamic society, and how this theory was able to predict many of the current events and possible future events using social and historical approaches. The paper consists of four parts as follows: First, an overview of Ibn-khaldun’s theory of social change and its philosophy is provided. Second, the role of human factors in social change according to Ibn-khaldun is explored. Third, natural factors affecting social change according to Ibn-khaldun are discussed. Finally, the impact of Covid-19 on our way of life in relation to Ibn-khaldun’s theory of social change is examined.